The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/maco.201910802
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate‐reducing bacteria‐assisted hydrogen‐induced stress cracking of 2205 duplex stainless steels

Abstract: The paper presents the results of a laboratory investigation of the microbiologically assisted hydrogen‐induced stress cracking (HISC) of 2,205 duplex stainless steel (DSS). The testing of susceptibility toward HISC was performed with two different methods. Precharged in sulfate‐reducing bacteria (SRB), inoculated medium samples were subjected to slow strain‐rate testing in artificial seawater. In situ constant load tests were performed directly in SRB‐inoculated medium under hydrogen charging at 70% of the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…These studies largely focused on the corrosion behaviors of carbon steel in sulfate‐reducing bacteria (SRB)‐containing suspension. [ 10,11 ] Sun et al [ 12 ] pointed out that the corrosion rate of Q235 with SRB was higher than that without SRB. They found that the cathodic current density of steel immersed in the soil with SRB was larger than that without SRB.…”
Section: Introductionmentioning
confidence: 99%
“…These studies largely focused on the corrosion behaviors of carbon steel in sulfate‐reducing bacteria (SRB)‐containing suspension. [ 10,11 ] Sun et al [ 12 ] pointed out that the corrosion rate of Q235 with SRB was higher than that without SRB. They found that the cathodic current density of steel immersed in the soil with SRB was larger than that without SRB.…”
Section: Introductionmentioning
confidence: 99%
“…In a paper [11], a mini-review was done giving the available information on SRB-assisted cracking of pipe steels in the presence of hydrogen. The effect of hydrogen on the SRB life, as well as the combined effect of hydrogenation and biocorrosion on the strength and ductility of steels, was studied in [12]. The exhaustion of steel ductility and embrittlement of its structure makes it especially relevant to study the influence of the microrelief shape on the stress concentration in local microregions of the surface.…”
Section: Introductionmentioning
confidence: 99%